Microwave device modelling using novel algorithms - Belen, Aysu (My University, 2021)
Intelligence Transportation Systems (ITS) is a research field in which researchers study methods and solutions to overcome problems of transportation systems in an environment friendly, low cost, and sustainable ways to reach maximum efficiency in transportation systems. The main aim of the studies of ITS is to reduce the work load of human personnel and possible human mistakes during all operation process. Todays, by means of the developments in ITS, their applications become widespread. Today many vehicles are actively using Global Position System (GPS), Wireless network communication (Wi-Fi, WiMAX, WiBro) or mobile networks (4G, 4.5G, 5G, LTE), RF or IR waves etc. are being used for machine to machine or machine- person communications, where one of the main constituents is availability of the high performance antennas. In fact, with the ever increasing need of technology and complexity of systems and their environment, need of high performance microwave antenna designs are also increased. This encourages microwave engineers to study for novel methods of modelling and prototyping to meet the high demands of communication industry. In this thesis, it was aimed at proposing novel design methodologies and technologies to meet the current unfilled antenna demands for Intelligence Transportation Systems. Thus four different types of antenna were studied: I. Patch Loaded Traveling Wave Antenna (PLTWA), II. Microstrip SIW antenna, III. Multilayer dielectric loaded lens antenna, IV. A large scale Reflectarray antenna with flat gain characteristics. Design stages and realizations of these antennas can briefly be summarized as follows: Firstly the antenna models are built up either by using 3D EM simulation tools or by Artificial Neural Network (ANN)s trained by the data sets created via 3D EM simulation tools, then these models are utilized via meta-heuristic optimization algorithms in the design stage to be ready in the realization where prototypes are produced using 3D printing technology as high performance and low cost antennas. Finally measurements have also been made for the comparison of the theoretical and experimental performance of the prototype antennas to be sure for the target to be realized. As conclusion we are glad to present our novel antenna designs in use of communication industry including Intelligence Transportation Systems to meet their current unfilled demands.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Microwave; Antenna; Microstrip antenna; Reflectarray; Beam scaning; Substrate integrated waveguide; Lens antenna; Intelligence transportation systems